2004
DOI: 10.1158/0008-5472.can-04-2231
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Protein Expression Detected by Mass Spectrometry Predict Tumor Response to Molecular Therapeutics

Abstract: Biomarkers that predict therapeutic response are essential for the development of anticancer therapies. We have used matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) to directly analyze protein profiles in mouse mammary tumor virus/HER2 transgenic mouse frozen tumor sections after treatment with the erbB receptor inhibitors OSI-774 and Herceptin. Inhibition of tumor cell proliferation and induction of apoptosis and tumor reduction were predicted by a >80% reduction in thymosin ␤4 and ub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 31 publications
4
107
0
Order By: Relevance
“…The majority of significantly changed peaks were observed in the low mass regions of the mass spectra and it may be suggested that many of these peaks are fragments of larger functional proteins. To date, there is little work performed in glioma focused on finding markers for early tumour detection (Liu et al, 2005), and in the general field of oncology there are only a few studies on finding markers for quantification of treatment efficacy (Gadducci et al, 2004;Reyzer et al, 2004). Such a marker could be of considerable clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of significantly changed peaks were observed in the low mass regions of the mass spectra and it may be suggested that many of these peaks are fragments of larger functional proteins. To date, there is little work performed in glioma focused on finding markers for early tumour detection (Liu et al, 2005), and in the general field of oncology there are only a few studies on finding markers for quantification of treatment efficacy (Gadducci et al, 2004;Reyzer et al, 2004). Such a marker could be of considerable clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen prostate tumor xenograft tissue samples corresponding to each treatment group: (a) control, (b) 25 mg/kg AEE788 (c) 25 mg/kg AEE788 + XRT (3 Gy), were harvested at 24 h and after 5 days of consecutive treatment, prepared, and MALDI-TOF mass spectra were acquired on a Voyager DE-STR mass spectrometer (Applied Biosystems, Foster City, CA, USA) following specifications previously described (37,38).…”
Section: Maldimentioning
confidence: 99%
“…MALDI profiling and imaging has already been successfully applied to samples ranging from individually captured cells [11,12], to intact organs, and whole animal sagittal sections [1]. Although a relatively young method, tissue analysis by imaging mass spectrometry (IMS) has been used to address a number of clinical questions in cancer [13,14], neurodegenerative diseases [15][16][17], organ development [18] and the study of drug and metabolite distribution [19][20][21]. Due to the variety of applications and the potential of tissue analysis by MALDI mass spectrometry to offer solutions directed at difficult problems in diagnostic and prognostic medicine, tissue profiling and imaging will continue to be an important topic of research.…”
Section: Introductionmentioning
confidence: 99%